2023
DOI: 10.1108/ijwbr-10-2022-0041
|View full text |Cite
|
Sign up to set email alerts
|

Wine consumer typologies based on level of involvement: a case of Turkey

Haluk Koksal,
Arian Seyedimany

Abstract: Purpose The purpose of this study is to segment Turkish wine customers based on their level of involvement. This study profiles them based on their wine drinking motivations, wine attributes, information sources, wine purchasing and consumption behaviour and socio-demographic characteristics. Design/methodology/approach For this study, a structured online questionnaire was used to collect data from the listed email addresses of institutes, universities and commercial websites. The sample size was 708 people.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
3
2
0
Order By: Relevance
“…These findings contribute to the uniqueness of this study, and we recommend consideration of this scale for studies where time is a constraint (such as with online surveys), yet capturing measure of the wine involvement construct is desired. In agreement with other recent findings for table wine (e.g., [22,43]), our results show that SW consumers can be segmented according to level of wine involvement. Importantly, our segmentation yielded actionable characteristics for marketers and retailers.…”
Section: Market Segmentation Based On Involvementsupporting
confidence: 93%
See 4 more Smart Citations
“…These findings contribute to the uniqueness of this study, and we recommend consideration of this scale for studies where time is a constraint (such as with online surveys), yet capturing measure of the wine involvement construct is desired. In agreement with other recent findings for table wine (e.g., [22,43]), our results show that SW consumers can be segmented according to level of wine involvement. Importantly, our segmentation yielded actionable characteristics for marketers and retailers.…”
Section: Market Segmentation Based On Involvementsupporting
confidence: 93%
“…In broad agreement with one study [22], but in contrast with another for table wine [27], we found that low-involvement consumers were less likely to identify endorsements as important and high-involvement consumers were more likely to select them as important. The discrepancy with the latter study [27] may reflect a genuine difference attributable to wine style (SW vs. Shiraz table wine), or possibly changes in consumers themselves over the approx.…”
Section: Purchase Cues Interact With Wine Involvementsupporting
confidence: 88%
See 3 more Smart Citations